A Soper Record Cairn from Baffin Island, N.W.T. - Stenton, Douglas R. (ARCTIC, 1986)
Two documents were recovered from a cairn located at the northern extremity of Nettilling Lake, Baffin Island. They record the details of J. Dewey Soper's winter expedition to Foxe Basin in 1926 and the travel itinerary of an Inuit hunting party.Key words: arctic exploration, Baffin Island, archaeology, cairns, Dewery Soper, Nettilling Lake Mots clés: exploration de l'Arctique, île de Baffin, archaéologie, cairns, Dewery Soper, Lac Nettilling